Small molecule MIRA-1 induces in vitro and in vivo anti-myeloma activity and synergizes with current anti-myeloma agents - Saha, M N (Nature Publishing Group, 2014)
BACKGROUND: Small molecule MIRA-1 induced mutant p53-dependent apoptosis in several types of solid tumours. However, anti-tumour activity of MIRA-1 in haematological malignancies including multiple myeloma (MM) is unknown. In this study, we evaluated the effect of MIRA-1 in MM. METHODS: We examined the anti-tumour activity of MIRA-1 alone or in combination with current anti-myeloma agents in a panel of MM cell lines, primary MM samples, and in a mouse xenograft model of MM. RESULTS: MIRA-1 treatment resulted in the inhibition of viability, colony formation, and migration and increase in apoptosis of MM cells irrespective of p53 status accompanied by upregulation of Puma and Bax and downregulation of Mcl-1 and c-Myc. Genetic knockdown of p53 did not abrogate apoptotic response of MIRA-1. MIRA-1 triggered activation of PERK and IRE-α leading to splicing of XBP1 indicating an association of endoplasmic reticulum stress response. Furthermore, combined treatment of MIRA-1 with dexamethasone, doxorubicin or velcade displayed synergistic response in MM cells. Importantly, MIRA-1 alone or in combination with dexamethasone retarded tumour growth and prolonged survival without showing any untoward toxicity in the mice bearing MM tumour. CONCLUSIONS: Our data provide the preclinical framework for clinical evaluation of MIRA-1 as a novel therapeutic agent to improve patient outcome in MM.